SEMAI: Sembilan Nilai Anti Korupsi dalam Pendidikan Anak Usia Dini - Fira Mubayyinah (Universitas Al-Hikmah Indonesia, 2017)
Corruption is a word that almost every day appears in the media both print and electronic media. Corruption nowadays is so familiar to our ears both for adults, teenagers, even children on elementary school they have often heard and read the word corruption. Although the moment is not necessarily all understand the meaning of corruption. Corruption is an extraordinary crime, so its eradication must also done with extraordinary efforts as well. One of the efforts to minimize the generation that has corrupt behavior then is extraordinary prevention efforts early. One way to do that is to conduct the character based education with anti corruptive behavior. This becomes very important as an effort to prevent corrupt behavior from the “bottom up” way, and with still continue the “top down” way. Formulating some learning model with high integrity value content, urged to be done with creativity to put the blue print of character in children that full with moral and spiritual values.